Namuncurá Marine Protected Area: an oceanic hot spot of benthic biodiversity at Burdwood Bank, Argentina - Schejter, Laura; Rimondino, Clara Mariana; Chiesa, Ignacio Luis; Díaz de Astarloa, Juan Martín; Doti, Brenda Lía; Elias, Rodolfo; Escolar, Mariana; Genzano, Gabriel Nestor; López Gappa, Juan José; Tatian, Marcos; Zelaya, Diego Gabriel; Cristobo, Javier; et al. (Polar Biology)
The first open-sea (non-coastal) Marine Protected Area (MPA) in Argentina was created in 2013 (and named “Namuncurá”), at Burdwood Bank, an undersea plateau located about 200 km south from Malvinas/Falkland Islands, SW Atlantic Ocean. This contribution represents the most recent and complete checklist of benthic organisms (mainly mega and macrofauna) that summarized 240 taxa collected at three sites in the mentioned area. The benthic richness here documented largely exceeds the values coming from other productive areas in Argentinean waters. Faunistic composition was different among the sites, although several species were shared. Bryozoans presented the highest richness compared to the other groups, followed by mollusks and sponges. These data represent valuable information and a very helpful starting point for incoming research, conservation efforts and management. It is essential to establish the spatial distribution of indicator taxa, like corals, sponges and bryozoans, to better attempt at the protection of benthic biodiversity in this rich Argentinean marine system. This is a key issue considering the notable extension of the MPA compared to other areas in Argentina, the bathymetric variations, particular oceanographic conditions and different fishing circumstances within the area. Fil: Schejter, Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencia Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Rimondino, Clara Mariana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Diversidad y Ecología Animal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto de Diversidad y Ecología Animal; Argentina Fil: Chiesa, Ignacio Luis. Consejo Nacional de Investigaciones Científicas y Técnicas. ...